Durability of pulmonary vein isolation following cryoballoon ablation: Lessons from a large series of repeat ablation procedures. (June 2022) - Mugnai, Giacomo; Cecchini, Federico; Stroker, Erwin; Paparella, Gaetano; Iacopino, Saverio; Sieira, Juan; De Greef, Yves; Tomasi, Luca; Bolzan, Bruna; Bala, Gezim; Overeinder, Ingrid; Almorad, Alexandre; et al.
Abstract: Introduction: The second-generation cryoballoon (CB) has emerged in the last decade as an effective treatment for atrial fibrillation (AF). This study sought to analyze the rate of PV reconnection following CB ablation, evaluate the most frequent PV sites of conduction recovery and finally to assess procedural and biophysical indicators of reconnection in a large cohort of patients undergoing repeat ablation for recurrence of atrial arrhythmias. Methods and Results: A total of 300 consecutive patients (189 males, 63%; mean age 63.0 ± 11.1 years) underwent a repeat ablation after 18.2 ± 10.8 months from the index CB ablation. All repeat ablations were performed using a 3-dimensional electro-anatomical mapping system. Among all 1178 PVs, 209 (17.7%) showed a late PV reconnection in 177 patients (1.18 per patient), at the time of repeat ablation procedure. Overall, persistent PV isolation could be documented in 969 of 1178 PVs (82.3%). In 123 of 300 patients (41%), persistent isolation could be demonstrated in all PVs, whereas PV reconnection could be documented in 177 patients (59%). In the multivariable analysis, nadir temperature (p = 0.03), time to PV isolation (p = 0.01) and failure to achieve − 40 °C within 60 s (p = 0.05) were independently associated with late PV reconnection. Conclusions: The rate of late PV reconnection after CB ablation was low (1.18 PVs/patient). The most frequent sites of reconnections were the superior-anterior portions for the upper PVs and the inferior-posterior portions for the lower PVs. Faster time to isolation, colder nadir temperatures and achievement of − 40 °C within 60 s were associated with durable PV isolation.